1995
DOI: 10.1111/j.1476-5381.1995.tb16642.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of KC399, a newly synthesized K+ channel opener, on acetylcholine‐induced electrical and mechanical activities in rabbit tracheal smooth muscle

Abstract: 4 In O-escin-skinned strips, Ca2+ (0.3-10 gM) produced a contraction in a concentration-dependent manner. KC399 (0.1 gM) had no effect on the Ca2 -force relationship in the presence or absence of ATP with GTP. However, at a very high concentration (1 gM), this agent slightly shifted the relationship to the right and attenuated the maximum Ca2+-induced contraction. 5 We conclude that, in rabbit tracheal smooth muscle, the membrane hyperpolarization induced by KC399 attenuates the ACh-induced tonic increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…IbTX exhibits greater specificity for such channels (Galvez et al, 1990;Suarez-Kurtz et al, 1991). In canine trachealis muscle ChTX (100 nM) evoked depolarization in excess of 10 mV (Kamei et al, 1994). This finding may indicate that, in canine trachealis muscle, BKCa channels are open under resting conditions and help to determine the resting membrane potential.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…IbTX exhibits greater specificity for such channels (Galvez et al, 1990;Suarez-Kurtz et al, 1991). In canine trachealis muscle ChTX (100 nM) evoked depolarization in excess of 10 mV (Kamei et al, 1994). This finding may indicate that, in canine trachealis muscle, BKCa channels are open under resting conditions and help to determine the resting membrane potential.…”
Section: Discussionmentioning
confidence: 85%
“…This finding may indicate that, in canine trachealis muscle, BKCa channels are open under resting conditions and help to determine the resting membrane potential. However, the experiments of Kamei et al (1994) were not carried out in the presence of an atropine-like drug and it is therefore possible that the depolarizing effect of the toxin was a consequence of the toxin directly or indirectly activating muscarinic cholinoceptors on the smooth muscle cells. In the studies of Fleischmann et al (1993) (Murray et al, 1991;present study (Murray et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…administration of pentobarbitone (35 mg kg-') and exsanguinated. Segments of tracheal smooth muscle were prepared for all experiments as previously described (Kamei et al, 1994). Briefly, circular muscle strips were excised from the cervical part of the trachea and immediately placed in Krebs-Henseleit solution.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the K+ channel openers, the relaxant effect of these agents on carbachol-induced contraction is reported to be weaker in guinea-pig than in human preparations (Taylor et al, 1988;Imagawa et al, 1993). Recently, we have reported that in the dog tracheal smooth muscle tissues, the action of K+ channel openers shows greater similarity to human bronchi than to guinea-pig tracheal smooth muscle (Kamei et al, 1994).…”
Section: Introductionmentioning
confidence: 97%
“…However, since the K ATP channel seems not to be so important in airway smooth muscle, few studies, except for those of Challiss et al [4] and Kamei et al [5], have evaluated the effects of K ATP channel openers on the airway smooth muscle of bovines or dogs. These authors found that K ATP channel openers inhibited inositol phosphate or IP 3 accumulations.…”
Section: Introductionmentioning
confidence: 99%